2003
DOI: 10.1002/jobm.200390007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of co‐cultivation on expression of the antifungal protein in Aspergillus giganteus

Abstract: The afp gene of Aspergillus giganteus encodes a small, highly basic polypeptide with antifungal activity, named Antifungal Protein (AFP). The protein is secreted by the mould and inhibits the growth of various filamentous fungi. In this paper we report that co-cultivation of A. giganteus with various microorganisms alters afp expression. It was found that co-cultivation modulates afp expression on the level of transcription, using a reporter system based on the beta-glucuronidase gene. The presence of Fusarium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…In agreement with this hypothesis, it has been shown that levels of AFP are highest during stationary phase, i.e. when nutrients become limiting, and that afp transcription is enhanced by heat shock, osmotic stress, carbon starvation and by the presence of certain cocultivants Meyer and Stahl 2003). In addition, it is most interesting that the AFP titre is significantly increased under high pH conditions (pH 8), as the pH within soil is mostly alkaline .…”
Section: Introductionsupporting
confidence: 61%
“…In agreement with this hypothesis, it has been shown that levels of AFP are highest during stationary phase, i.e. when nutrients become limiting, and that afp transcription is enhanced by heat shock, osmotic stress, carbon starvation and by the presence of certain cocultivants Meyer and Stahl 2003). In addition, it is most interesting that the AFP titre is significantly increased under high pH conditions (pH 8), as the pH within soil is mostly alkaline .…”
Section: Introductionsupporting
confidence: 61%
“…Therefore, mixed cultivation is expected to have advantages over mono-cultivation for higher substrate utilization, productivity, adaptability for the growth environment and contamination resistance (Dwivedi et al, 2011). Meyer and Stahl (2003) revealed that the impact of co-cultivation were strongly dependent on the medium composition, which affected the co-growth of mixed fungi, leading to enhanced carbon source utilization. Yang (1993) conducted a cocultivation using different molds and yeasts, and found that the co-cultivation of mixed molds could enhance protein enrichment, whereas the mixed yeast and mold did not demonstrate supportive biomass growth.…”
Section: Co-cultivationmentioning
confidence: 99%
“…Within or between different species, the reaction of microbes for existence of other cell types can be sensed [41]. Microorganisms in co-culture systems can interconnect through uninterrupted cell to cell interactions or via signal molecules in media [42]. The Sde 2-40 bacterium can produce proteins containing many cadherin and cadherin-like domains.…”
Section: Growth Of Sde 2-40 B Cereus and Co-culture On Agarose Andmentioning
confidence: 99%